Comparative Analysis of Factors Affected on the Development of Retail in the Russian Federation ("Journal "U". Economy. Management. Finance.", 2017)
This article considers main business trends and possible future problems of the retail business in Russia. The opportunities for this type of business in the Russian Federation are identified by comparative analysis of different historical periods. This analysis has also helped to reveal the efficiency of the retail business and its possible influence on the Russian economy.
Keywords: retail; trading networks; trademarks networks; commodity circulation; consumers; suppliers